Analisis Perbedaan Tarif Riil dengan INA-CBG'S Pelayanan Operasi Bedah Plastik di Rumah Sakit Universitas Andalas - Fory Fortuna; Yurniwati Yurniwati; Rima Semiarty (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Since BPJS Kesehatan and INA-CBG’s were being applied in Indonesia, various groups were worried about the difference phenomenon with the real rates invented by previous researchers. Plastic surgery services at UNAND Hospital have fluctuated in the last three years. The phenomenon of the difference between the real RS rates and the large INA-CBG's rates was also found. The purpose of the study was to see and to describe the differences between real rates and INA-CBG's in reconstructive plastic surgery patients at UNAND Hospital. This study used secondary data from medical records of 72 cases. The independent variables consist of age, gender, insurance class, action class, length of stay, service, drugs/BMHP, real hospital rates and INA-CBG's rates. The variable that depends on this research is the difference between the real RS rate and the INA-CBG's rate. Characteristics of respondents with an average age of 28,20 ± 19,88 years, more men than women (59.7%:40.3%, n=72), average length of stay was 2,34±1,95 days, average cost of medicine/BMHP was Rp. 884,968, -, average services cost was Rp. 2,393,800. The most treatment class used was class 3, with the most treatment done was khusus 1. Length of stay, operation class and drug/BMHP were significantly related to the difference in both rates (p=0.00, p=0.012, p=0.00). The conclusion that there was a significant difference between the real hospital rates and INA-CBG's rates in plastic surgery cases at UNAND Hospital. Length of stay, class of operation and drug/BMHP were significantly related to the difference in rates. Keywords: Real Rates, INA-CBG's Rates, Service Cost Component  ABSTRAK Sejak BPJS kesehatan dan INA-CBG’s diberlakukan, berbagai kalangan khawatir karena ditemukannya beberapa fenomena selisih tarif oleh peneliti terdahulu. Pelayanan bedah plastik di RS UNAND mengalami fluktuasi tiga tahun terakhir. Ditemukan juga fenomena selisih antara tarif riil RS dengan tarif INA-CBG’s yang besar. Tujuan dari penelitian ini adalah untuk melihat perbedaan antar tarif riil dan INA-CBG’s pada pasien bedah plastik rekonstruksi di RS UNAND. Metode penelitian: Penelitian ini menggunakan data sekunder yaitu sebanyak 72 kasus. Variabel independen terdiri atas umur, jenis kelamin, kelas jaminan, kelas tindakan, lama rawat, jasa pelayanan, obat/BMHP, tarif riil RS dan tarif INA-CBG’s. Variabel dependen pada penelitian ini adalah selisih tarif riil RS dengan tarif INA-CBG’s. Hasil pada penelitian ini didapatkan rerata umur dalam tahun yaitu 28,20 ± 19,88, laki-laki lebih banyak dari perempuan (59,7%:40,3%, n=72), rerata lama rawat 2,34±1,95 hari, rerata biaya obat Rp.884,968,-, rerata jasa pelayanan Rp.2,393,800. Kelas rawatan terbanyak adalah kelas 3, dengan tindakan terbanyak adalah khusus 1. Kesimpulan dari penelitian ini adalah terdapat perbedaan bermakna antar rerata tarif riil dengan INA-CBG’s (p=0,00). Lama rawat, kelas tindakan dan obat/BMHP berhubungan signifikan dengan selisih tarif. Kata Kunci: Tarif Riil, Tarif INA-CBG’s, Komponen Biaya Pelayanan